2010
DOI: 10.1021/ja103631u
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Claisen Rearrangement Catalyzed by N-Heterocyclic Carbenes

Abstract: In the presence of a chiral azolium salt (10 mol %), enols and ynals undergo a highly enantioselective annulation reaction to form enantiomerically enriched dihydropyranones via an N-heterocyclic carbene catalyzed variant of the Claisen rearrangement. Unlike other azolium-catalyzed reactions, this process requires no added base to generate the putative NHC-catalyst, and our investigations demonstrate that the counterion of the azolium salt plays a key role in the formation of the catalytically active species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
130
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(141 citation statements)
references
References 52 publications
5
130
1
5
Order By: Relevance
“…Interestingly, the generation of 1,3-biselectrophile (II) has been reported from a,b-unsaturated acyl fluorides by Lupton et al, [10] from ynals by Bode et al and Xiao et al [11] and from enals with an oxidant by Studer et al [12] In this communication, we wish to report the generation of a,b-unsaturated acylazolium from bromoenal and the enantioselective reaction with 1,3-dicarbonyl compounds. During the preparation of this manuscript, You et al and Xiao et al reported the enantioselective reaction of a,b-unsaturated acylazolium generated in situ from enals and ynals, respectively.…”
mentioning
confidence: 98%
“…Interestingly, the generation of 1,3-biselectrophile (II) has been reported from a,b-unsaturated acyl fluorides by Lupton et al, [10] from ynals by Bode et al and Xiao et al [11] and from enals with an oxidant by Studer et al [12] In this communication, we wish to report the generation of a,b-unsaturated acylazolium from bromoenal and the enantioselective reaction with 1,3-dicarbonyl compounds. During the preparation of this manuscript, You et al and Xiao et al reported the enantioselective reaction of a,b-unsaturated acylazolium generated in situ from enals and ynals, respectively.…”
mentioning
confidence: 98%
“…Enantioselective reaction of KA derivatives with ynals 93 catalyzed by N -heterocyclic carbenes 95 was described by Kaeobamrung et al 91 Reactions were carried out using N -mesityl substituted precatalyst 95 in toluene at 40…”
Section: Scheme 35mentioning
confidence: 99%
“…Erste Berichte über Claisen-artige NHC-katalysierte Reaktionen wurden parallel von Lupton et al [26] und Bode et al [27] publiziert. Interessanterweise postulierten beide Gruppen komplett unterschiedliche Mechanismen für solche Transformationen: Lupton et al gingen von einem Mecha- [28] in Gegenwart von Triazol-5-yliden und in der vinylogen Reaktion mit Ketiminen 34 [29] Das dritte Hauptattribut der N-heterocyclischen Carbene ist ihre Basizität.…”
Section: Nhc-katalysierte Transformationenunclassified